The Experience of Becoming a Straight Ally-Activist of GLBT People - Matthew Eichler (Adult Education Research Conference, 2007)
This hermeneutic phenomenological investigation uncovers elements of the experience of becoming an ally-activist. Six essential themes are developed through writing and analysis of interview text.